Talent Management Development Strategy in Improving Human Resources Quality Towards Society 5.0 Era: Literature Review - Zega, Arnol Wandra; Aprinawati, Aprinawati; Tanjung, Mijy Swandi; Nainggolan, Agustina; Amalia, Delvi Dede; Manik, Enjelia; Sinaga, Mulyati Patresia; Kabeakan, Siat Putri (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
In facing the Era of Society 5.0, companies must prepare human resources with qualified performance, by managing talent management. Talent management is a series of very important stages when managing human resources (HR) in a company. Talent management can be the right strategy and can be used by companies to develop every human resource in the company. The purpose of this study is to provide an understanding of the importance of talent management strategies in order to realize the improvement of the quality of human resources in achieving the goals of the company. Talent management requires the right strategies to improve the competence of employees in the company. The strategies in question include: identifying talent needs, using technology in the recruitment process, training programs and competency development. This study also explains examples of case studies of companies that have implemented talent management in the company.